The Intersecting Roles of Religion, Culture, and Spirituality in Emancipatory Adult Education - Nadira K. Charaniya; Jane West Walsh; Felicia Brown-Haywood; Elizabeth J. Tisdell (Adult Education Research Conference, 2010)
This paper discusses why considering the intersection of religion, spirituality, and culture is important in emancipatory education efforts and provides discussion of approaches for doing so in practice.